2017
DOI: 10.2298/zmspn1733143b
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of genets in population of saprotrophic fungi Marasmius rotula on Mt. Stara planina

Abstract: This study was conducted to determine the size and spatial distribution of mycelial individuals of Marasmius rotula at one locality on Mt. Stara planina in the Republic of Serbia. Total of 12 sporocarps were collected from investigated locality (Vidlič, Stara planina). Sporocarps were distributed in four groups and distances between them were approximately 10-30 meters. Genomic DNA was extracted from each sporocarp and used for inter-simple sequence repeat (ISSR) polymorphism analysis using (GTG) 5 and (GACA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…The banding patterns obtained by both primers for samples MR3, MR6, and MR8 were not completely congruent, but they were grouped into the same genet. Out of all seven identified genets, four were represented by only one sporocarp, thus it was not possible to determine their approximate diameters, while other three had diameters ranging from 2 to 4 m. These results are in agreement with our previous study [11] where three distinct genets were identified from an area of similar size as in the present study. The approximate sizes of the two genets identified in the study of Bošković et al [11] were 2 m in diameter and one even appeared to be 15 m in diameter.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The banding patterns obtained by both primers for samples MR3, MR6, and MR8 were not completely congruent, but they were grouped into the same genet. Out of all seven identified genets, four were represented by only one sporocarp, thus it was not possible to determine their approximate diameters, while other three had diameters ranging from 2 to 4 m. These results are in agreement with our previous study [11] where three distinct genets were identified from an area of similar size as in the present study. The approximate sizes of the two genets identified in the study of Bošković et al [11] were 2 m in diameter and one even appeared to be 15 m in diameter.…”
Section: Discussionsupporting
confidence: 91%
“…Out of all seven identified genets, four were represented by only one sporocarp, thus it was not possible to determine their approximate diameters, while other three had diameters ranging from 2 to 4 m. These results are in agreement with our previous study [11] where three distinct genets were identified from an area of similar size as in the present study. The approximate sizes of the two genets identified in the study of Bošković et al [11] were 2 m in diameter and one even appeared to be 15 m in diameter. Results from both studies indicate that even though they colonize distinct substrates, the genets of M. rotula can occupy relatively large areas of the forest floor.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations